Landscape in Motion: Nostalgia and Urban Redevelopment in Ed Ruscha's Then & Now: Hollywood Boulevard, 1973-2004. (November 2015) - Reynolds, Matt
Ed Ruscha's photo book Then & Now: Hollywood Boulevard, 1973-2004 consists of two continuous photographic panoramas of the north and south sides of the eponymous street taken thirty years apart. The juxtaposition of these two time periods depicts a dramatic transformation of the neighborhood, a result of the ongoing Hollywood Redevelopment Project (HRP). From its inception in 1986, the HRP has enlisted a nostalgic image of the city during the heyday of the film industry to mobilize redevelopment efforts. At first glance, Then & Now seems complicit in the HRP's nostalgic enterprise. However, Ruscha's book provides a device for rethinking the city's renewal and the historical narratives that drive it. "Reading" this unusual text disrupts our relationship to "now" and "then, " problematizing nostalgia's function as a condition of Hollywood's revitalization and urban redevelopment more broadly.